2013
DOI: 10.1186/1471-2121-14-28
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-induced gradual phenotypic modulation of cultured human glomerular epithelial cells may be independent of Wilms’ tumor 1 (WT1)

Abstract: BackgroundRenal podocytes form the main filtration barrier possessing a unique phenotype maintained by proteins including podocalyxin and nephrin, the expression of which is suppressed in pathological conditions. We used an in vitro model of human glomerular epithelial cells (HGEC) to investigate the role of high glucose in dysregulating the podocytic epithelial phenotype and determined the time needed for this change to occur.ResultsIn our in vitro podocyte system changes indicating podocyte dedifferentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…Chronic hyperglycaemia disrupts signal transduction pathways involved in glomerular survival [36]. Our previous work [37], as well as work by others [38] demonstrated a decrease of glomerular nephrin expression as an early event in hyperglycaemic conditions. We demonstrated herein that short-term exposure of isolated glomeruli to high glucose affected nephrin expression and impaired phosphorylation and Akt activation.…”
Section: Discussionmentioning
confidence: 84%
“…Chronic hyperglycaemia disrupts signal transduction pathways involved in glomerular survival [36]. Our previous work [37], as well as work by others [38] demonstrated a decrease of glomerular nephrin expression as an early event in hyperglycaemic conditions. We demonstrated herein that short-term exposure of isolated glomeruli to high glucose affected nephrin expression and impaired phosphorylation and Akt activation.…”
Section: Discussionmentioning
confidence: 84%
“…Hyperglycaemia is a major determinant for the development of diabetic microvascular disease [ 38 ] and patients with diabetes experience increased glucose uptake by the kidney [ 39 ]. Previous work of our lab has shown that HG induced partial de-differentiation of podocytes [ 40 ] and apparently impaired foot processes by severe downregulation of podocalyxin [ 41 ]. We presently provided evidence that the presence of HG suffices to downregulate insulin signaling in vitro in human podocytes, as well as ex vivo , in isolated rat glomeruli.…”
Section: Discussionmentioning
confidence: 99%
“…PODXL has been reported to upregulate and form a complex with the glucose-transporter 3 (GLUT3) in embryonal carcinoma cancer stem cells [134]. On the other hand, glucose has been found to modulate PODXL expression in both normal and malignant cells [27,135,136]. In HGEC human glomerular epithelial cells, the presence of high-glucose levels downregulated PODXL expression [135,136], which reverted to normal values after cell exposure to low-glucose conditions [136].…”
Section: Podxl In Cancer Cell Metabolismmentioning
confidence: 99%
“…On the other hand, glucose has been found to modulate PODXL expression in both normal and malignant cells [27,135,136]. In HGEC human glomerular epithelial cells, the presence of high-glucose levels downregulated PODXL expression [135,136], which reverted to normal values after cell exposure to low-glucose conditions [136]. Accordingly, we observed that Raji Burkitt lymphoma cells cultured in low-glucose conditions (0.5 mM) expressed increased surface levels of PODXL compared to those grown in high-glucose conditions (11 mM) [27].…”
Section: Podxl In Cancer Cell Metabolismmentioning
confidence: 99%